Conserved hypothalamic c-Fos activation pattern induced by the mGlu5 receptor antagonist MPEP during peri-pubertal development in mice - Inta, Ioana; Bettendorf, Markus; Gass, Peter (Pharmacopsychiatry, 2016)
Introduction: 2-Methyl-6-(phenylethynyl)pyridine (MPEP) is a selective mGlu5 receptor (mGluR5) antagonist intensively studied as potential novel anxiolytic drug. In the adult, MPEP activates stress-related areas, including the paraventricular nucleus of the hypothalamus (PVNh). However, it is unknown if MPEP targets similar structures in the juvenile brain as well.Methods: Here we examined by immunohistochemical methods the induction pattern of the neuronal activity marker c-Fos by MPEP at peri-pubertal stages (postnatal day P16, P24, P32 and P40) in C57BL6/N mice.Results: Despite the previously reported sharply diminished hypothalamic mGluR5 expression during postnatal development, we found a highly conserved PVNh activation by MPEP together with c-Fos expression in the extended amygdala. Interestingly, MPEP also robustly activated the paraventricular nucleus of the thalamus (PVT) and suprachiasmatic nucleus (SCN), regions associated with the modulation of circadian rhythms. Discussion: These results indicate a conserved activation pattern induced by MPEP in the young vs. adult brain especially in brain areas regulating stress and circadian rhythms and may be of importance regarding the effect of mGluR5 antagonists in the treatment of mood disorders during juvenile development.